2007
DOI: 10.1007/s10529-006-9290-5
|View full text |Cite
|
Sign up to set email alerts
|

Expression and characterization of recombinant human micro-plasminogen

Abstract: Micro-plasminogen (microPlg) gene amplified from human liver cells by reverse transcription PCR was inserted into expression vector pET-28a (pET-28a/microPlg) and transformed into E. coli strain BL21(DE3). Recombinant human micro-plasminogen (rh-microPlg) was over-expressed as inclusion bodies when induced with IPTG. After renaturation and purification, 16 mg rh-microPlg/l was obtained with a homogeneity of 95% (w/w). Pro-urokinase (proUK)-induced rh-microPlg activation was significantly faster than when Glu-p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 18 publications
(16 reference statements)
0
8
0
Order By: Relevance
“…Human VDAC clones (Genecopeia, Germantown, MD) were expressed in Escherichia coli and purified as previously described (20). Recombinant human microplasminogen (Genecopeia) was expressed in E. coli and purified from clones as previously described (21). Recombinant murine GRP78 and the COOH-terminal domain of GRP78 containing amino acids 516 -636 (Lys 516 -Gly 636 ), a kind gift from Dr. Sylvie Y.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Human VDAC clones (Genecopeia, Germantown, MD) were expressed in Escherichia coli and purified as previously described (20). Recombinant human microplasminogen (Genecopeia) was expressed in E. coli and purified from clones as previously described (21). Recombinant murine GRP78 and the COOH-terminal domain of GRP78 containing amino acids 516 -636 (Lys 516 -Gly 636 ), a kind gift from Dr. Sylvie Y.…”
Section: Methodsmentioning
confidence: 99%
“…The velocity of S-2288 hydrolysis was calculated as the increase of absorbance at 405 nm using a Molecular Devices SPECTRAmax kinetic plate reader. The molar extinc-tion coefficient (⑀) of p-nitroanilide at 405 nm is 10,000 M Ϫ1 cm Ϫ1 (21). The kinetic parameters (K m ,V max , and k cat ) were calculated using the GraphPad Prism 6 program from GraphPad Software, Inc.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…144 The molecule has been recombinantly expressed in E. coli, Pichia pastoris, and insect cells. 149,150,151 It showed 100 times lesser inhibition by a2-antiplasmin than plasmin due to the absence of the lysine binding sites in micro-plasmin. 150 It does not have any kringle domain and thus lacks fibrin affinity.…”
Section: Direct Thrombolytic Agentsmentioning
confidence: 97%
“…Sequence analysis has shown that the NH 2 terminal portion of the plasminogen molecule, which becomes the heavy (A) chain after activation, contains homologous domains referred to as 'kringles' [3]. It appears that the kringles contain lysine-binding sites which are involved in the interaction of plasmin with fibrin and a-2-antiplasmin [4][5][6][7][8]. The fibrinolytic activity in human plasma was subsequently shown to depend on activation of a plasminogen as precursor.…”
Section: Introductionmentioning
confidence: 99%